When can professional sport recommence safely during the COVID-19 pandemic? Risk assessment and factors to consider - Carmody, S.; Murray, A.; Borodina, M.; Gouttebarge, V.; Massey, A. (British Journal of Sports Medicine, 2020)
The COVID-19 pandemic has had, and will have, profound effects on every person on earth. Measures advocated by the WHO and put in place by national governments, businesses and individuals will save millions of lives, but current movement restrictions (ie, various degrees of lockdown) cannot continue indefinitely. The activity restrictions imposed by governments are designed to reduce human-to-human transmission; they buy time and allow international collaboration between governments and internally to build and allocate the resources and systems to